Effects of outsourcing employment services: evidence from a randomized experiment - Helge Bennmarker; Erik Grönqvist; Björn Öckert (Institute for Labour Market Policy Evaluation (IFAU), 2009)
In many countries welfare services that traditionally have been provided by the public sector are increasingly being contracted out to private providers. But are private contractors better at providing these services? We use a randomized experiment to empirically assess the effectiveness of contacting out employment services to private placement agencies. Our results show that unemployed at private placement agencies have a much closer interaction with their placement worker than unemployed at the Public Employment Service (PES). In particular, unemployed at private agencies receive more assistance in improving their job search technology. We do not find any overall difference in the probability of employment between private placement agencies and the PES), but this hides important heterogeneities across different types of unemployed. We find evidence that private providers are better at providing employment services to immigrants, and also indications that they may be worse for adolescents. Any effects tend to fade away over time.
Keywords: J68; 330; Job placement; Contracting out; Arbeitsvermittlung; Privatwirtschaft; Öffentlicher Sektor; Dienstleistungsqualität; Schweden